Assessing the influence of Mathematics in Teaching and Learning Physics Subject in Secondary Schools in Tanzania - Malaki, Sospeter Shikulu (International Journal of Scientific Research and Management (IJSRM), 2021)
Learning Mathematics is a key fundamental in every education system that aims to prepare its citizens for a productive life in the 21st century. As a nation, the development of a highly-skilled and well-educated manpower is critical to support an innovation and technology-driven economy. A strong grounding in Mathematics and a talent pool in Mathematics are essential to support the wide range of value-added economic activities and innovations. In this vein, a study intended to assess the influence of Mathematics in teaching and learning Physics, a case study of secondary education. A study was guided by two specific objectives; to determine the applications of Mathematics in Physics and to investigate the relationship between Mathematics and Physics. The qualitative and quantitative approaches were used in getting categorical and numerical data in line with the triangulation research design employed. Students and science teachers were targeted in the collection of data which made a total of 60 participants. The questionnaire, observation and documentary review were key devices used in data collection processes. The collected data were analyzed by using SPSS and the research findings revealed that there is statistically very strong positive relationship between Mathematics and Physics. . In other words, the influence of Mathematics in Physics subject is enormous to the extent that students are encouraged not  to drop Mathematics in their early classes. This will assist to increase number of Tanzanian engineers and geologists in various sectors for extracting our natural resources.